PERFORMANCE ANALYSIS BETWEEN INTERPRETED LANGUAGE-BASED (LARAVEL) AND COMPILED LANGUAGE-BASED (GIN) WEB FRAMEWORKS - Yang, Jason Aaron; Aklani, Syaeful Anas (Universitas Putera Batam, 2023)
Web frameworks are essential for web developers, allowing them to build web applications more efficiently and effectively. This research paper compared two web frameworks with different programming language implementations: interpreted programming language and compiled programming language. PHP/Laravel was chosen as the representative interpreted programming language, and Go/Gin was chosen as the representative compiled programming language, because they were the most popular based on their star counts on GitHub. Based on a research paper by the University of Minho, Go was nearly 10 times faster than PHP in terms of execution time. Despite this, PHP is still the most commonly used web technology among the top 1 million websites. The results of a series of tests comparing the two showed that Gin was over 86 times faster than Laravel in terms of requests per second and time per request. The choice of which web framework to use will depend on the specific needs and goals of the project. However, if performance is the only criterion, then Gin is a better choice than Laravel.